ARAB DEVELOPMENT AID AND THE NEW DYNAMICS OF MULTILATERALISM: TOWARDS BETTER GOVERNANCE? - Evren Tok; Rachael Calleja; Hanaa El-Ghaish (European Scientific Journal, ESJ, 2014)
This study attempts to explore the evolution of the Arab Development Aid and contextualizes the Arab model of development aid vis-à-vis the DAC Model and the Southern Model shedding light on its transforming characteristics. The Kingdom of Saudi Arabia (KSA), Kuwait and the United Arab Emirates (UAE) have been among the most active donors in the world, with official development assistance (ODA) averaging 1.5 percent of their combined gross national income (GNI) during the period 1973-2008, more than twice the United Nations target of 0.7 percent and five times the average of the OECD-DAC countries. This paper approaches this model of development aid by focusing on: the changing nature of multilateral development framework and the rising role of emerging economies in the aid system; the basic tenets of the Arab aid development model and its current composition and characteristics; the challenges and future prospects for the Arab development aid and its potential role in engendering better governance mechanisms in the Arab region and globally with a case study on the case of the Qatar Development Fund.